Spremembe v gostoti energije magnetnega polja Zemlje med geomagnetno nevihto G5 11. maja 2024 - Čop, Rudi (Geodetski vestnik, 2024)
Geomagnetic storms are the largest disturbance in the Earth's magnetic field. On May 11, 2024, a geomagnetic storm occurred at the peak of the 25th solar cycle, reaching the highest level (G5) on the planetary scale. On that day, a geomagnetic storm was also measured at the PIA geomagnetic observatory (Piran, Slovenia), reaching the maximum possible value of the geomagnetic index K = 9. Such strong geomagnetic storms occur on average every 40 to 60 years. A geomagnetic storm with an index of K = 9 represents an important reference for all disturbances in the local magnetic field from different sources and different intensities. Therefore, an analysis of accelerations in the energy density of the local magnetic field during the first 150 days in 2024 was made. The identified effects of geomagnetic storms with different K indices will serve to better analyse disturbances in the local magnetic field that have occurred in the past years and will happen in the future.
Keywords: accelerations in the energy density; energy density in the local magnetic field; geomagnetic indices; geomagnetne nevihte; geomagnetni indeksi; magnetno polje; severe geomagnetic storm; solar cycles; Sonce; sončevi cikli; Zemlja